Statistical Process Control Approach in the Evaluation of Sowing Quality in Corn Cultivation in Tokat-Kazova - Engin Özgöz; Ebubekir Altuntas; Abdullah Kasap (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to evaluate of the quality of the sowing process applied by 10 different producers in their fields in Tokat / Kazova, in the cultivation of grain corn, by Statistical Process Control. In determining of the quality of the sowing process, plant spacing uniformity, seeding depth uniformity and ratio of plant emergence were used. Acceptable plant spacing, the multiples ratio and the miss ratio were determined for planting spacing uniformity on the row. Plant emergence ratio values varied between 59.60% (D field) and 93.13% (B field) in the trial areas. Acceptable plant spacing, the multiples ratio and the miss ratio values ranged from 65.56% - 90.24%, 4.02 - 15.69% and 5.11% - 12.91%, in the trial areas, respectively. It was concluded that the sowing process is generally ‘Moderate’ and ‘Inadequate’ according to the parameters of plant spacing uniformity. Similarly, individual and moving range quality charts prepared for statistical quality control of plant spacing uniformity and seeding depth uniformity showed that the sowing process was not under control. According to these results, it is necessary to take precautions regarding the factors that negatively affect the quality of the sowing process for sustainable agricultural production.